Modern aspects of treatment of allergic rhinitis - D. V. Shabanov (Медицинский совет, 2019)
The importance of allergic diseases is due to their increasing prevalence in both developed and developing countries. The prevalence of allergic diseases in most countries of the world is 10–30% among urban and rural population. In the regions of Russia, the prevalence of allergic diseases reaches 19–40% among the adult population and over 27% among children and adolescents. The article deals with the main aspects of the pathogenesis of allergic rhinitis as the most common allergic pathology. The features of antihistamine therapy with modern drugs of the 2nd generation and their influence on the links of the inflammatory process are considered. The data of studies of the effectiveness and safety of the original drug bilastine. Given the use cases bilastine in clinical practice.